Snakes and Ladders Game Media on the Behavior of Brushing Teeth in Elementary School Children - Putri, Rifa Fauziah Syaifia; Setyawati, Baby Prabowo; Wiranto, Deni; Nurwanti, Widi (Journal Center of Excellent : Health Assistive Technology, 2024)
Background: One way to keep your teeth and mouth clean is by brushing your teeth regularly and regularly. Good habits and discipline in caring for and cleaning teeth by brushing teeth regularly and regularly must be started early so that future generations are accustomed to a healthy lifestyle. Brushing your teeth is cleaning your teeth from dirt or food residue using a toothbrush. Purposes: to determine the effectiveness of the snake and ladder game media on tooth brushing behavior in Grade 5 children at Susukan 06 Elementary School. Methods: This study uses a survey method with an approachpre-post design. The sample in this study were 30 grade 5 students at Susukan 06 Elementary School, East Jakarta total sampling. Result: The results of the study show that if the significance value of knowledge, attitudes and actions is 0.000, this value is less than 0.05 which can then be said if Ha is accepted and H0 is rejected, which means there is a difference between the results pre test and post test knowledge, attitudes and actions of respondents so that it can also be concluded that there is an effective effect of education through snakes and ladders games on tooth brushing behavior. Conclusion: There is an increase in knowledge, attitudes and actions, this is evidenced by the variable value using the wilcoxon test is at a p-value of 0.000.